A detailed comparison of third-party funding regulations in Hong Kong and Singapore. Issue 1 (2nd January 2021) - Eken, Can
ABSTRACT: Third-party funding (TPF) has played a major role in international arbitration over the last decade. Despite uncertainties and continuing discussions on whether TPF should be regulated, Singapore and Hong Kong successively passed laws to legalize and regulate TPF, and both jurisdictions have become leading pioneers globally. This can be largely attributed to their competition with each other to be Asia's leading arbitration centre, and by regulating the use of TPF, they have moved closer to this goal. However, even though both wish to ensure the legality of TPF in international arbitration, their laws and the consequences of non-compliance differ dramatically in each jurisdiction. Moreover, although these two jurisdictions are leading arbitration centres, their laws on TPF have not yet been analysed thoroughly in the existing scholarship. This article aims to fill the gap, following the comparative law methodology and analysing the rules on TPF in Hong Kong and Singapore. It also aims to investigate the advantages and disadvantages of the laws adopted differently by the two jurisdictions and answer two important questions: (i) What laws could create better conditions for funders? and (ii) What can be done to improve those conditions?